2022
DOI: 10.1101/2022.03.23.485460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From neural border to migratory stage: A comprehensive single cell roadmap of the timing and regulatory logic driving cranial and vagal neural crest emergence

Abstract: Neural crest cells exemplify cellular diversification from a multipotent progenitor population. However, the full sequence of molecular choices orchestrating the emergence of neural crest heterogeneity from the embryonic ectoderm remains elusive. Gene-regulatory-networks (GRN) govern early development and cell specification towards definitive neural crest. Here, we combine ultra-dense single cell transcriptomes with machine-learning and large-scale experimental validation to provide a comprehensive GRN underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…The NC is a multipotent and migratory cell population unique to vertebrates and essential notably for pigment, peripheral and enteric nervous system, and craniofacial structures formation [ 24 ]. For the input data, we used whole embryo scRNA-seq datasets for the Xenopus tropicalis, a non-amniote tetrapod vertebrate, at an early developmental stage (late gastrulation stage 12, and neurulation stages 13 (neural plate) and 14 (neural fold)) and Mus musculus, a mammal, at a similar developmental stage (late gastrulation stage 8.25) [ 20 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The NC is a multipotent and migratory cell population unique to vertebrates and essential notably for pigment, peripheral and enteric nervous system, and craniofacial structures formation [ 24 ]. For the input data, we used whole embryo scRNA-seq datasets for the Xenopus tropicalis, a non-amniote tetrapod vertebrate, at an early developmental stage (late gastrulation stage 12, and neurulation stages 13 (neural plate) and 14 (neural fold)) and Mus musculus, a mammal, at a similar developmental stage (late gastrulation stage 8.25) [ 20 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…3000 genes were chosen as the optimal number because it strikes a balance between minimizing the batch effect and still maintaining a sufficient number of genes to accurately classify cell types. Thus, this is part of the domain adaptation that we perform to make the resulting model less dependent on the number of genes that are missing in another dataset to which the model will be applied (e.g., 30% of the genes considered crucial for training a NC classifier on frog data were absent from the zebrafish dataset [ 20 ]). Additionally, to reduce the effect of the different biological domains between datasets, and to reduce the effect of the scRNA-seq data sparsity, we apply a sigmoid function that smooths expression units in a more flexible manner than simple binarization, which has been shown to keep enough information for scRNA-seq data analysis [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The neuro-epithelial border cells (NEBs) form a transient embryonic cell population. Investigations on the transcriptional state of vertebrate NEBs by scRNA-seq analyses in several vertebrate models (i.e., zebrafish, Xenopus , chicken) have shown that NEBs express the NEB-specific gene regulatory network (GRN: PAX3 / 7 , ZIC1 , MSX1 / 2 , TFAP2 , ZNF703 ) ( Figure 3 A) together with ectodermal-lineage specifiers ( SOX2 / 3 , GMNN , LHX5 ) [ 37 , 96 , 97 ]. These studies thus propose that NEBs initially transit through an ectodermal state.…”
Section: Reprogramming Capacity Of Developmental Potential Guardians ...mentioning
confidence: 99%